Adapting to Disruption : How Consumer Behavior and Digital Innovation Transform the European Publishing Landscape - Qurku, Krisel; Kania, Karolina Anna; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis examines how digital change is affecting the reading habits and expectations of Generation Z in Europe. It looks at how younger readers choose what to read, which formats they prefer, and what role discovery tools like social media play. It also explores how publishers are adapting to these changes. The research follows a mixed-methods approach. First, a survey collected quantitative data from European readers. This was followed by consumer interviews to explore the reasons behind their choices in more depth. Expert interviews with publishing professionals offered a view into current industry strategies. By combining these perspectives, the research connects reader behavior with publisher responses and highlights areas where the two are misaligned. The goal is to identify clear, practical steps that publishing houses can take to stay relevant in accordance with the readers’ expectations and needs.
Vedoucí práce: Karolina Anna Kania
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses